Metode pelatihan pembuatan Edugame dalam pembelajaran Sekolah Dasar - Dwiningrum, Siti Irene Astuti; Rukiyati, Rukiyati; Murti, Rahayu Condro; Setyawan, Siti Luzviminda Harum Pratiwi; Utami, Anindita Ayu Nisa (Universitas Negeri Yogyakarta, 2024)
According to UNESCO, the literacy level in Indonesia is still relatively low, with a reading interest index of 0.001. This shows that only one in 10,000 children in Indonesia is interested in reading. Improving literacy is challenging because it requires a comprehensive strategy, especially related to cultural literacy. Increasing cultural literacy is influenced by the learning process. Students who have good cultural literacy will have the capital to learn and be ready to face future challenges related to cultural diversity. The ability to adapt in learning is an important aspect that teachers and students must have in the era of the Fourth Industrial Revolution. Elementary school teachers' ability to adapt to technological devices influences digital literacy skills. Therefore, resilience is needed to adapt positively in the digital era when faced with various kinds of problems. The aim of this PKM is to assist the Primary School Teacher Working Group (SD KKG) in increasing students' digital resilience and literacy in Bantul Regency, DIY.